2016
DOI: 10.1155/2016/8145926
|View full text |Cite
|
Sign up to set email alerts
|

Intrastromal Injection of China Painting Ink in Corneas of Male Rabbits: Clinical and Histological Study

Abstract: Background. Many patients with corneal opacity or complicated cataract in blind eye ask for cosmoses. In this study we tried to investigate the staining of corneas of male rabbits by Rotring China painting ink and to study the histological changes. Method. 10 eyes of 10 male Baladi Egyptian rabbits were injected (0.1 mL) intrastromally in the cornea by the use of China painting ink (Rotring Tinta China) through insulin syringe (27-gauge needle) by single injection; clinical follow-up is for 6 months and lastly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Despite establishing the long-term safety of rotring ink in animal and human studies, its ocular or systemic toxicity cannot be ruled out and every attempt should be made to prevent its inadvertent intraocular entry. [ 11 16 ] Lack of intraoperative perforation in any of our patient could be mainly attributed to the use of i-OCT during lamellar dissection. However, even previous studies on intrastromal tattooing conducted without the aid of i-OCT have not reported any perforation till date.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Despite establishing the long-term safety of rotring ink in animal and human studies, its ocular or systemic toxicity cannot be ruled out and every attempt should be made to prevent its inadvertent intraocular entry. [ 11 16 ] Lack of intraoperative perforation in any of our patient could be mainly attributed to the use of i-OCT during lamellar dissection. However, even previous studies on intrastromal tattooing conducted without the aid of i-OCT have not reported any perforation till date.…”
Section: Discussionmentioning
confidence: 88%
“…The site of tattooing was marked using disposable trephines, especially in cases of localized tattooing. [ 16 ] A 4 mm partial thickness clear corneal incision aimed at 50% depth (the depth was decided based on prior studies) was created 1 mm away from the limbus with a microcrescent knife (Sharpoint, Surgical Specialties Corporation, Wyomissing, PA; USA). This was appreciated on i-OCT as a hyporeflective pocket surrounded by hyperreflective stromal layers on either side.…”
Section: Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have concluded that corneal tattooing using china ink is considered durable with permanent effect as it is engulfed by keratocytes [ 8 , 12 ] or endocytosed by corneal fibroblasts [ 17 ]. Some other theories proposed stability due to the fact that the cornea has no lymphatics, and thus, there is no diffusion or dispersion [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Rotring painting ink (Rotring Ink, Hamburg, Germany) (also known as China ink) was packed in a sterile glass infusion bottle for 20 minutes in a steam autoclave at 121°C. One of the authors (AHA) has previously demonstrated the safety and efficacy of using the same type of Rotring painting ink used in our study on male rabbits [ 12 ]. The stain color used was the black for all eyes.…”
Section: Methodsmentioning
confidence: 99%